Associations between quantitative evaluation of bowel wall microvascular flow by contrast‐enhanced ultrasound and indices of disease activity in Crohn's disease patients using both bolus and infusion techniques. Issue 8 (25th July 2019) - Zezos, Petros; Zittan, Eran; Islam, Shadman; Hudson, John; Ben‐Bassat, Ofer; Nazarian, Amin; Steinhart, Hillary A.; Silverberg, Mark S.; Atri, Mostafa
Abstract: Purpose: The aim is to investigate whether baseline contrast‐enhanced ultrasound (CEUS) correlates with indices of activity in Crohn's disease (CD) and can predict response to medical treatment. Methods: In this prospective study, symptomatic CD patients underwent baseline CEUS performed with Definity using both bolus and infusion methods. Time‐intensity curves (TIC), peak intensity (PI), and area under curve (AUC) from a region of interest over the diseased bowel were calculated for both bolus and infusion acquisitions. We used Mann‐Whitney U test for continuous and chi‐square/two‐tailed Fisher's exact test for categorical variable comparison and Spearman's correlation coefficient to correlate clinical score and CEUS kinetic parameters. Results: Twenty‐one patients (9 men, 12 women, median age 32 years) were accrued. Fifteen patients had clinically active disease defined as Harvey‐Bradshaw Index (HBI) score ≥5. Median values of baseline CEUS parameters PI (bolus: 26 vs 8.86; P = .023 and perfusion: 7.6 vs 3.2; P = .009) and AUC (bolus: 769 vs 248.8; P = .036 and perfusion: 188.9 vs 73.9; P = .012) differed significantly in patients with active vs inactive disease. Nine patients with active disease underwent escalated or new treatment. Five were nonresponders. Responders had higher median values of baseline parameters (PI, bolus: 35 vs 18.8; P = .556, and perfusion: 7.6 vs 3.9; P = 190), (AUC, bolus: 1473.9 vs 314; P = .111, and perfusion: 154.7 vs 74.4, P = .286). Conclusions: CEUS kinetic parameters correlate with clinical and laboratory indices and are significantly higher in patients with active disease. The responders had higher CEUS kinetic parameters than nonresponders that did not reach statistical significance in our small cohort.